On local gradient estimates for anisotropic elliptic and parabolic equations - Skrypnik, I.I.; Skrypnik, S.V. (Труды Института прикладной математики и механики, 2012)
It is considered wide class of anisotropic elliptic and parabolic equations. Sharp local pointwise estimates for gradient of solutions of such equations are established.